Impact of the COVID-19 Pandemic on Antibiotic Prescribing by Dentists in Galicia, Spain: A Quasi-Experimental Approach - Almudena Rodríguez-Fernández; Olalla Vázquez-Cancela; María Piñeiro-Lamas; Adolfo Figueiras; Maruxa Zapata-Cachafeiro (Antibiotics, 2022)
Background: Antibiotic resistance is one of the most pressing public health problems. Health authorities, patients, and health professionals, including dentists, are all involved in its development. COVID-19 pandemic restrictions on dental care may have had repercussions on antibiotic prescribing by dentists. The aim of this study was to assess the impact of the COVID-19 pandemic on antibiotic prescribing by dentists, and to review antibiotic consumption according to the WHO Access, Watch, Reserve classification. We conducted a natural, before-and-after, quasi-experimental study, using antibiotic prescription data covering the period from January 2017 to May 2021. A segmented regression analysis with interrupted time series data was used to analyse the differences between the numbers of defined daily doses (DDD) of antibiotics prescribed monthly. The outcomes showed an immediate significant decrease in overall antibiotic prescribing by primary-care dentists during lockdown, followed by a non-significant upward trend for the next year. This same pattern was, likewise, observed for Access and Watch antibiotics. COVID-19 pandemic restrictions on dental care influenced the prescription of antibiotics. During confinement, an initial decrease was observed, this trend changed when in person consultations were recovered. It might be beneficial to analyse the prescription of antibiotics using the WHO AWaRe classification, in order to monitor their appropriate use.